(untitled) (Nativa, 2025)
Desenvolvimento de filmes biodegradáveis de amido de milho reforçados com nanocelulose para embalagens de alimentos This research evaluated blends of six essential oils (EOs) to maximize their antimicrobial effect without compromising sensory acceptability, aiming to inhibit Pseudomonas aeruginosa (ATCC 33152), Salmonella enteritidis (ATCC 13076), Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Klebsiella aerogenes (ATCC 35029), Listeria monocytogenes (ATCC 19114), Aspergillus brasiliensis (ATCC 16404), and Aspergillus niger (ATCC 6275). Thirty-one mixtures of six essential oils: eucalyptus (Eucalyptus globulus Labill.), basil (Ocimum basilicum L.), geranium (Pelargonium graveolens L’Hér.), rosemary (Salvia rosmarinus Spenn.), oregano (Origanum vulgare L.), and lemongrass (Cymbopogon citratus (DC.) Stapf) were proposed and evaluated by measuring the inhibition halo of microbial growth. Through optimization, four new mixtures were evaluated at 100% concentration and four at 5% concentration. Semi-trained panelists assessed these new blends for the most palatable combination by qualitatively selecting their organoleptic properties. Several blends showed desirability values above 0.90, reaching a maximum of 0.9499 for oregano. However, the blend containing rosemary (0.93%), eucalyptus (1.82%), oregano (94.95%), and lemongrass (2.3%) was selected for having the highest average sensory acceptance in terms of desirability ranking and taste preference. All tested samples inhibited fungal growth. The chosen blend showed total inhibition of K. aerogenes and inhibition halos greater than 30 mm for S. typhimurium, E. coli, S. aureus, and L. monocytogenes. Keywords: essential oils; antimicrobial; sensory acceptability; microbial inhibition; optimization; desirability. RESUMO: Esta pesquisa avaliou misturas de seis óleos essenciais (OEs) para maximizar seu efeito antimicrobiano sem comprometer a aceitabilidade sensorial, visando inibir Pseudomonas aeruginosa (ATCC 33152), Salmonella enteritidis (ATCC 13076), Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Klebsiella aerogenes (ATCC 35029), Listeria monocytogenes (ATCC 19114), Aspergillus brasiliensis (ATCC 16404) e Aspergillus niger (ATCC 6275). Trinta e uma misturas de seis óleos essenciais: eucalipto (Eucalyptus globulus Labill.), manjericão (Ocimum basilicum L.), gerânio (Pelargonium graveolens L’Hér.), alecrim (Salvia rosmarinus Spenn.), orégano (Origanum vulgare L.) e capim-limão (Cymbopogon citratus (DC.) Stapf) foram propostas e avaliadas medindo o halo de inibição do crescimento microbiano. Por meio da otimização, quatro novas misturas foram avaliadas na concentração de 100% e quatro na concentração de 5%. Os painelistas semitreinados avaliaram essas novas misturas para a combinação mais palatável, selecionando qualitativamente suas propriedades organolépticas. Várias misturas apresentaram valores de desejabilidade acima de 0,90, atingindo um máximo de 0,9499 para orégano. Entretanto, a mistura contendo alecrim (0,93%), eucalipto (1,82%), orégano (94,95%) e capim-limão (2,3%) foi selecionada por ter a maior aceitação sensorial média em termos de classificação de desejabilidade e preferência de sabor. Todas as amostras testadas inibiram o crescimento fúngico. A mistura escolhida apresentou inibição total de K. aerogenes e halos de inibição maiores que 30 mm para S. typhimurium, E. coli, S. aureus e L. monocytogenes. Palavras-chave: óleos essenciais; antimicrobiano; aceitabilidade sensorial; inibição microbiana; otimização; desejabilidade.